A Bright Future for Protein Kinase D1 as A Drug Target to Prevent or Treat Pancreatic Cancer. (2nd January 2016) - Liou, Geou-Yarh; Storz, Peter; Leitges, Michael
Abstract: Pancreatic ductal adenocarcinoma originates from acinar cells that undergo acinar-to-ductal metaplasia (ADM). ADM is initiated in response to growth factors, inflammation, and oncogene activation and leads to a de-differentiated, duct-like phenotype. Our recent publication demonstrated a transforming growth factor α-Kras G12D -protein kinase D1-Notch1 signaling axis driving the induction of ADM and further progression to pancreatic intraepithelial neoplasia. This suggests that protein kinase D1 might be an early marker for tumor development and a potential target for drug development.